2015
DOI: 10.1186/s13039-015-0143-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of next-generation sequencing for 24-chromosome aneuploidy screening of human preimplantation embryos

Abstract: BackgroundAneuploidy is a leading cause of repeat implantation failure and recurrent miscarriages. Preimplantation genetic screening (PGS) enables the assessment of the numeral and structural chromosomal errors of embryos before transfer in patients undergoing in vitro fertilization. Array comparative genomic hybridization (aCGH) has been demonstrated to be an accurate PGS method and in present thought to be the gold standard, but new technologies, such as next-generation sequencing (NGS), continue to emerge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 32 publications
(37 reference statements)
1
53
0
Order By: Relevance
“…Many studies also showed that NGS has become an efficient and robust technology for PGD/PGS [67][68][69]. For example, one study reported 24 healthy births after NGS testing [70] and another one resulting in a healthy birth to the parents carrying Robertsonian translocation after NGS-based PGD [71].…”
Section: Next Generation Sequencing (Ngs)mentioning
confidence: 95%
“…Many studies also showed that NGS has become an efficient and robust technology for PGD/PGS [67][68][69]. For example, one study reported 24 healthy births after NGS testing [70] and another one resulting in a healthy birth to the parents carrying Robertsonian translocation after NGS-based PGD [71].…”
Section: Next Generation Sequencing (Ngs)mentioning
confidence: 95%
“…On the other hand, qPCR does not use WGA, can identify aneuploidies in a rapid fashion but has lower genomic coverage, is not able to distinguish small deletions and duplications and cannot detect structural chromosome aberrations or mosaicisms . NGS is the newest platform for PGT‐A that permits to reduce DNA sequencing cost, increases number of samples that can be simultaneously sequenced, detects unbalanced translocations, partial aneuploidies and enhances the detection of mosaicisms . The higher rate of mosaicism detected by NGS is probably explained by a superior sensitivity of this method for detecting minor lines in mixed cell populations compared with aCGH .…”
Section: Weaknessesmentioning
confidence: 99%
“…23 NGS is the newest platform for PGT-A that permits to reduce DNA sequencing cost, increases number of samples that can be simultaneously sequenced, detects unbalanced translocations, partial aneuploidies and enhances the detection of mosaicisms. 24,25 The higher rate of mosaicism detected by NGS is probably explained by a superior sensitivity of this method for detecting minor lines in mixed cell populations compared with aCGH. 26 Even so, depending on the depth of sequencing and the specific NGS platform used, the sensitivity for detecting cytogenetically distinct subpopulations of cells varies as NGS strategies change.…”
Section: Cumulative Ivf Outcomesmentioning
confidence: 99%
“…Next generation sequencing (NGS) is a technology that requires optimized DNA amplification to reduce the introduction of artifacts during the amplification process [49,50]. Following the DNA amplification, artifacts can be identified and removed by bioinformatics software.…”
Section: Next Generation Sequencingmentioning
confidence: 99%